2020
DOI: 10.1002/hed.26541
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of intraparotid lymph node metastasis in primary parotid cancer: Systematic review

Abstract: Background The prognostic importance of intraparotid lymph node metastasis (P+) in patients with primary parotid gland carcinoma is unclear. Methods Nineteen retrospective and noncomparative cohort studies, published between 1992 and 2020, met the inclusion criteria and included 2202 patients for this systematic review. Results The pooled prevalence of the P in adult patients in the unselected studies was 24.10% (95% confidence interval = 17.95‐30.25). The number of P+ lymph nodes per patient was counted in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
(135 reference statements)
2
23
0
1
Order By: Relevance
“…A recent systematic review including studies until 2020 revealed a mean pooled prevalence of the PAR+ rate of 24% [ 12 ]. The number of PAR+ lymph nodes varied from 1 to 11 in these hospital-based studies, which fits to the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review including studies until 2020 revealed a mean pooled prevalence of the PAR+ rate of 24% [ 12 ]. The number of PAR+ lymph nodes varied from 1 to 11 in these hospital-based studies, which fits to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year recurrence-free survival rate based on Kaplan–Meier analysis varied from 83% to 88% in PAR− patients, compared to 36% to 54% in PAR+. Only for studies allowed an OS analysis, the average calculated HR for a risk of death in patients with PAR+ compared to PAR− was increased by 2.14 [ 12 ]. In a newer analysis on major salivary gland cancer, the PAR+ rate was 21% and PAR+ 5-year OS rate was 57.6%, compared to 79.4% in PAR− patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent review on this topic raised the objection that intraparotid lymph node metastasis may not be first echelon lymph nodes for regional spreading in all cases. “It is imaginable that if the tumour is located in the far inferior part of parotid gland, level IIa or IIb lymph node metastasis might regularly occur without intraparotid lymph node metastasis” 46 . The study by Erovic et al 9 overcame this objection.…”
Section: Treatmentmentioning
confidence: 99%
“…For malignant tumours, FS enables stratification between lymphomas and primary parotid gland carcinomas as well as “low-” and “high-grade” subtypes. Reliable FS information on the dignity of the parotid lesion should sustain further surgical measures, such as termination of surgery (for benign tumours) or continuation with removal of the whole parenchyma of the parotid gland (e.g., complete parotidectomy in cases with primary parotid malignant tumours) with elective neck dissection [ 11 , 12 , 13 ] and resection (as well as reconstruction) of the facial nerve in cases of nerve infiltration through a malignant lesion (other than lymphoma) [ 14 ]. Intraoperative evaluation of intraparotid lymph nodes could enable rationalised performance of complete parotidectomy and elective neck dissection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%